Toward efficient electrocatalytic degradation of iohexol using active anodes: A laser-made versus commercial anodes - Bomfim, Sthefany A.; Dória, Aline R.; Gonzaga, Isabelle M.D.; Oliveira, Rhayza Victoria Matos; Romão, Luciane P.C. [UNESP]; Salazar-Banda, Giancarlo R.; Ferreira, Luiz F.R.; Eguiluz, Katlin I.B. (Elsevier, 2022)
The X-ray iodinated contrast medium iohexol is frequently detected in aquatic environments due to its high persistence and the inefficiency of its degradation by conventional wastewater treatments. Hence, the challenge faced in this study is the development of an alternative electrochemical treatment using active anodes. We investigate the oxidation of iohexol (16.42 mg L−1) using different operating conditions, focusing on the role of different mixed metal oxide anodes in the treatment efficiency. The electrocatalytic efficiency of the Ti/RuO2–TiO2 anode prepared using a CO2 laser heating and an ionic liquid is compared with Ti/RuO2–TiO2–IrO2 and Ti/IrO2–Ta2O5 commercial anodes. The hypochlorite ions generated by the anodes are also analyzed. The effect of the electrolyte composition (NaCl, Na2SO4, and NaClO4) and current density (15, 30, and 50 mA cm−2) on the iohexol degradation is also studied. The Ti/RuO2–TiO2 laser-made anode is more efficient than the commercial anodes. After optimizing experimental parameters, this anode removes 95.5% of iohexol in 60 min and displays the highest kinetic rate (0.059 min−1) with the lowest energy consumption per order (0.21 kWh m−3order−1), using NaCl solution as the electrolyte and applying 15 mA cm−2. Additionally, iohexol-intensified groundwater was used to compare the efficiency of anodes. The Ti/RuO2–TiO2 is also more efficient in removing the organic charge from the real water matrix (21.7% TOC) than the commercial anodes. Notably, the iohexol removal achieved is higher than all electrochemical treatments already reported using state-of-the-art non-active anodes in lower electrolysis time. Therefore, data from this study indicate that the electrochemical degradation of iohexol using the Ti/RuO2–TiO2 anode is efficient and has excellent cost-effectiveness; thus, it is a promising approach in the degradation of iohexol from wastewater. Furthermore, the Ti/RuO2–TiO2 active anode is competitive and can be an excellent option for treating effluents contaminated with recalcitrant organic compounds such as iohexol.
Keywords: Electrochemical oxidation; Emerging contaminant; Iodinated contrast media; Mixed metal oxides